The zahir a novel of obsession - Coelho, Paulo (Thorsons, 2006)
The protagonist of this novel is a renowned author who writes about spirituality and once went on pilgrimage along the road to Santiago. On a return visit, he is abandoned by his wife, who leaves no trace of herself behind. As the story unfolds the author becomes obsessed with understanding the reason for her desertion.